Swimming capability of zebrafish is governed by water temperature, caudal fin length and genetic background - Wakamatsu, Yuma (Sci Rep, 2019)
Several zebrafish strains such as AB, Tübingen (TU), Wild India Kolkata (WIK) and Tupfel long fin (TL) have been established for genetic study. Each strain has its morphological and behavioral traits. Motor traits, however, have not been explored in zebrafish strains. We here applied a treadmill for fish (swimmill) and measured swimming capability of adult zebrafish by critical swimming speed, which is the maximum water velocity in which fish can keep swimming. First, we confirmed that swimming capability does not vary between female and male. Second, we found that the appropriate water temperature for swimming was between 16 and 30 °C. Third, our fin clip experiments using long-finned zebrafish revealed that they can exhibit high swimming capability when the caudal fin length was set between 3 and 10 mm, implying that long-finned zebrafish are unfavorable for fast swimming. Finally, we compared swimming capability of several zebrafish strains and demonstrated that WIK fish was significantly less capable of swimming despite that they have short caudal fin (~9 mm). The offspring of WIK fish were less capable of swimming, while hybrids of WIK and TU showed high swimming performance comparable to TU. Thus, lower swimming capability of WIK strain is inheritable as a motor trait.